TINJAUAN YURIDIS PENGATURAN ALAT BUKTI KETERANGAN AHLI DALAM PROSES PEMERIKSAAN PERSIDANGAN PIDANA - DS, Eben Ezer; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Expert information is a statement given by someone who has special expertiseabout what is needed to make the light of a criminal case for the purpose of examination.This is justified in the Criminal Procedure Code Article 1 point 28 and is recognized as alegitimate evidence of five evidences that can be used in the process of criminal evidencestipulated in Article 184 paragraph (1). This evidence was presented to assist the judge inbuilding his conviction before making a decision on the defendant in analyzing any factsthat were presented in the process of investigation and examination of the trial. However,the regulation of expert information in the Criminal Procedure Code has not yetarranged in a comprehensive and comprehensive manner regarding the criteria andexpert qualifications that can be presented, so that the implications for broadinterpretation by the parties who present experts and the reality raises problems incriminal trials specifically for judges in making decisions. The purpose of writing thisthesis, namely: First, To determine the arrangement of expert information in the CriminalProcedure Code compared to other legislation. Second, to find out the practice ofproviding evidence of expert testimony in the reality of criminal trials.This type of research can be classified as a type of normative legal research.This research is descriptive, namely a study that describes clearly and in detail about theregulation and reality of giving expert information in criminal proceedings. Data sourcesused secondary data consisting of primary legal material, legal material secondary, andtertiary legal materials, data collection techniques in this study with the library studymethod, after the data collected is then analyzed to draw conclusions.From the results of the research and discussion it can be concluded that, First,the arrangement of expert information in the KUHAP has not been fully andcomprehensively regulated so that it requires improvement with references from otherlaws and regulations. Second, the practice of providing evidence of expert testimony inthe reality of criminal proceedings has been presented by both parties in litigation.However, each expert is heavy / lame with the interests of the party that presents it. In theend each statement will give confusion to the judge.Keywords: Evidence Tools - Expert Information - Qualifications - Criminal Investigationand Trial Process.